The effects of repeated earthquake ground motions on the non-linear response of SDOF systems. - Amadio, C. (Earthquake engineering & structural dynamics.)
In many parts of the world, the repetition of medium strong intensity earthquake ground motions at brief intervals of time has been observed. The new design philosophies for buildings in seismic areas are based on multi level design approaches, which take into account more than a single damageability limit state. According to these approaches, a sequence of seismic actions may produce important consequences on the structural safety. In this paper, the effects of repeated earthquake ground motions on the response of single degree of freedom systems (SDOF) with non linear behaviour are analysed. A comparison is performed with the effect of a single seismic event on the originally non damaged system for different hysteretic models in terms of pseudo acceleration response spectra, behaviour factor q and damage parameters. The elastic perfect plastic system is the most vulnerable one under repeated earthquake ground motions and is characterized by a strong reduction of the q factor. A moment resisting steel frame is analysed as well, showing a reduction of the q factor under repeated earthquake ground motions even larger than that of an equivalent SDOF system.